Cutaneous Alternariosis in Immunosuppressed Patients Treated with Photodynamic Therapy and Oral Antifungals, a Synergistic Strategy - Pedro Gil-Pallares; Tamara Gracia-Cazaña; Marcial Álvarez-Salafranca; Marcos Antonio Gorgojo; Mar García-García; Antonio Beltrán-Rosel; Manuel Almenara-Blasco; Alba Navarro-Bielsa; Yolanda Gilaberte (MDPI AG, 2024)
Cutaneous alternariosis is a rare condition, more frequently presented in immunocompromised patients, which usually requires long courses of systemic antifungals that may interact with other medications. The presented series shows three cases of cutaneous alternariosis in immunocompromised patients and organ transplant recipients that were successfully treated with photodynamic therapy and oral antifungals, allowing a reduction in the systemic treatment duration and therefore decreasing the risk of side effects and drug interactions.